Corneal changes in type II diabetes mellitus in Malaysia - Choo, M.M.; Prakash, K.; Samsudin, A.; Soong, T.; Ramli, N.; Kadir, A.J. (Press of International Journal of Ophthalmology (IJO PRESS), 2010)
AIM: To compare corneal endothelial structure and central corneal thickness (CCT) between type II diabetics and non-diabetic control patients. To look for correlations between diabetic status and corneal findings. METHODS: Hospital-based, observational study. 200 eyes (from 100 type II diabetic patients and 100 controls) were included. Specular microscopy and pachymetry were used to measure endothelial cell density, size, coefficient of variation in cell area, hexagonality as well as corneal thickness. Independent t-tests were used to compare variables between diabetics and controls. Pearson correlation tests were used to evaluate correlations between corneal findings and diabetic status such as duration of diabetes, haemoglobin A1c (HbA1c) level and severity of diabetic retinopathy. RESULTS: Endothelial cell density in the diabetic group (2541.6 +/- 516.4 cells/mm(2)) was significantly lower than that in the control group (2660.1 +/- 515.5 cells/mm(2), P<0.05). The average size of endothelial cells, standard deviation (SD) of cell size and coefficient of variation (CV) of cell area were all significantly higher in diabetics. Hexagonality was significantly lower in diabetics (41.1% +/- 19.6%) compared to nondiabetics (45.2% +/- 20.6%). CCT was higher in diabetics but not significant (P>0.05). Duration of diabetes, HbA1c level and severity of diabetic retinopathy were not significantly correlated with corneal endothelial findings. CONCLUSION: Type II diabetes causes a significant alteration in the state of the cornea including reduction in endothelial cell density and increased pleomorphism and polymegathism. Central corneal thickness is unaffected.